The role of hilar lymphadenectomy in patients subjected to hepatectomy due to colorectal metastasis - Viana,Eduardo Freitas (2011)
CONTEXT: Hepatectomy is the treatment of choice for colorectal liver metastases, and several studies have shown good results, with 5-year survival rates ranging from 40% to 57%. Several clinical and pathological predictive factors for survival after liver resection have been studied. Involvement of the hepatic hilum lymph nodes, the incidence of which varies from 2% to 10%, indicates a poor long-term prognosis. RESULTS: Despite variable results, some authors have reported a not-insignificant improvement in survival rate in liver-metastasis patients with hilar lymph node involvement who undergo combined liver resection and lymphadenectomy. Due to the low rates of morbidity and mortality for liver-resection surgery, several specialized centers perform liver resections combined with lymphadenectomies in selected cases. It should be noted that the therapeutic value of systemic lymphadenectomy is not yet entirely understood, and only controlled studies comparing groups with and without lymphadenectomy can fully resolve the issue. CONCLUSION: In any case, hilar lymph node dissection has been shown to be a useful tool for improving the accuracy of extra hepatic disease staging, regardless of its impact on survival.